Characterisation of ball degradation events in professional tennis - Lane, B.; Sherratt, P.; Hu, X.; Harland, A. (Sports Engineering, 2017)
Tennis balls are acknowledged to degrade with use and are replaced at regular intervals during professional matches to maintain consistency and uniformity in performance, such that the game is not adversely affected. Balls are subject to the international tennis federation`s (ITF) ball approval process, which includes a degradation test to ensure a minimum standard of performance. The aim of this investigation was to establish if the ITF degradation test can assess ball longevity and rate of degradation and determine if there is a need for a new degradation test that is more representative of in-play conditions. Ball tracking data from four different professional events, spanning the three major court surfaces, including both men`s and women`s matches were analysed. The frequency of first serves, second serves, racket impacts and surface impacts were assessed and the corresponding distribution of ball speed and (for surface impacts) impact angle was determined. Comparison of ball impact frequency and conditions between in-play data and the ITF degradation test indicated the development of a new test, more representative of in-play data, would be advantageous in determining ball longevity and rate of degradation with use. Assessment of data from different surfaces highlighted that grass court subjected the ball to fewer racket and surface impacts than hard court or clay. In turn, this appears to influence the distribution of ball speed on impact with the surface or racket, suggesting a surface-specific degradation test may be beneficial. As a result of these findings a new test protocol has been proposed, utilising the in-play data, to define the frequency of impacts and impact conditions to equate to nine games of professional tennis across the different surfaces.